Pengaruh Kesulitan Keuangan dan Penyimpangan Akuntansi terhadap Agresivitas Pajak yang Dimoderasi Dewan Komisaris Independen - Shintyamani, Yogeswari Sista; Tjaraka, Heru (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
The objective of this study is to empirically examine the effects of financial distress and accounting irregularities on tax aggressiveness, with the moderating role of independent commissioners. The study targets manufacturing companies listed on the Indonesia Stock Exchange for the 2016–2019 period and 52 firms were selected, producing 208 firm-year observations. This study shows that companies experiencing financial pressure tend to adopt more aggressive tax practices. In contrast, accounting irregularities are not found to have a statistically significant effect on the level of tax aggressiveness. Another finding indicates that the presence of independent commissioners can dampen the influence of financial distress on tax aggressiveness. However, independent commissioners do not act as a moderating variable in the relationship between accounting irregularities and tax aggressiveness.